A Review of Grey Literature Cited by Food Loss Law and Policy Scholarship. Issue 1 (3rd April 2021) - Hackstadt, Angela
ABSTRACT: In the United States, state and federal programs, rules, and legislation attempt to address the social, economic, and environmental impacts of food waste. Research on the efficacy of these interventions rely on a variety of grey literature resources. Grey literature is valuable to policy research but may be overlooked because it is not published commercially and is often deemed unauthoritative. This review focuses on the use of grey literature in food waste law and policy scholarship to identify the most used sources and to determine what, if any, archiving strategies authors use. Recommendations for librarians and researchers are discussed. This article has been republished with minor changes. These changes do not impact the academic content of the article.